Countercultural sports and local policies: an approach from the theory of public policy networks (Deportes contraculturales y políticas locales: una aproximación desde la teoría de las redes de políticas públicas) - Marcen Muñio, Celia; Murillo Regaño, Rut; Arbones Arque, Irela; Pelegrín Paracuellos, José (Retos, 2019)
Abstract: The aim of this study was to analyze the degree of institutionalization of the so-called lifestyle sports in the city of Zaragoza, with the aim of establishing approach strategies between administration and users to improve both the practice of these sports modalities and the adequacy and management of their spaces of practice, from the theoretical framework of public policy networks. Through a qualitative methodology (semi-structured interviews, participant observation, and content analysis), 27 sports modalities were analyzed and allocated in a continuum based on their degree of institutionalization, communication channels between members, as well as the use of more or less fixed facilities or places for their practice. In the discussion of the results we reflect on the desired and undesired consequences of public policies implemented with respect to these sports modalities, as well as on the complex dialectic between institutional support and "domestication". Finally, action strategies are proposed based on the analysis performed. Resumen. El objeto de este estudio fue analizar el grado de institucionalización de los denominados lifestyle sports en la ciudad de Zaragoza, con la finalidad de establecer estrategias de acercamiento entre administración y usuarios que mejore tanto la práctica de estas modalidades deportivas como la adecuación y gestión de sus espacios de práctica, desde el marco teórico de las redes de políticas públicas. Mediante metodología cualitativa (entrevistas semiestructuradas, observación participante y análisis de contenido), se han analizado 27 modalidades deportivas, situándose en un continuum derivado de su grado de institucionalización, los canales de comunicación entre los miembros, así como la utilización de instalaciones o lugares más o menos fijos en su práctica. En la discusión de los resultados se reflexiona sobre las consecuencias deseadas e indeseadas de las políticas públicas implementadas respecto a estas modalidades deportivas, así como la compleja dialéctica entre el apoyo institucional y la “domesticación”. Finalmente se proponen estrategias de acción en función del análisis realizado.